PERBEDAAN IMPLEMENTASI INDOOR DAN OUTDOOR LEARNING TERHADAP HASIL BELAJAR IPA - Rani Cahyani; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
The aims of this study to understand the difference of the results learn science between conducted using indoor learning and outdoor learning. This study included in the kind of research quasi experiment. The research was conducted at Junior High Schools 11 Yogyakarta academic year 2014/2015 which consisted of 137 students. Of 4 class obtained class VIIB and VIIC. Technique the data collection was done with using a technique documentation and technique test. The results of the analysis by using uji-t show the data having value thitung = 2,830 with p = 0,006, because p < 0,01 so can be concluded that the difference very significant on the outcome of learning science between conducted using indoor leaning with outdoor learning